Integration of Papua into the Unitary State of the Republic of Indonesia - Bauw, Lily (Faculty of Law, Universitas Pekalongan, 2024)
The aim of this research is to show that the government and indigenous Papuan people must consider and discuss the possibility of integrating Papua into the territory of the Unitary State of the Republic of Indonesia. This research method is normative and empirical, with statutory regulations as the main source. The research results are then analyzed and can be justified by looking at the facts or reality in the field. The research results show that there is a lot of debate about the integration of Papua into the Republic of Indonesia as mentioned above, whether it is part of a political effort or state formation. The most important thing is to learn from the past, namely how to utilize differences to produce results that are beneficial to society, especially the Papuan people. Therefore, the most important thing to do is resolve human rights violations or acts of violence that occurred in Papua Province, both before and after integration.